2004
DOI: 10.1381/096089204322917864
|View full text |Cite
|
Sign up to set email alerts
|

Binge Eating, Quality of Life and Physical Activity Improve after Roux-en-Y Gastric Bypass for Morbid Obesity

Abstract: RYGBP resulted in significant improvements in disordered eating, weight-related QoL, and physical activity in addition to weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 36 publications
5
85
1
8
Order By: Relevance
“…Finally, bariatric surgery could also improve QoL in obese people by means of the educational programs provided to patients which reinforce self-confidence and self-esteem (Dymek et al, 2002). Gastric bypass may contribute to the control of previous eating behavioural disorders (Boan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, bariatric surgery could also improve QoL in obese people by means of the educational programs provided to patients which reinforce self-confidence and self-esteem (Dymek et al, 2002). Gastric bypass may contribute to the control of previous eating behavioural disorders (Boan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The Questionnaire is a validated and reliable instrument in obesity research and eating disorders and was already applied in LAGB, VBG and RYGBP [11][12][13][14][15][16]. This questionnaire measures three dimensions of eating behavior: cognitive restraint of eating, disinhibition of eating, and susceptibility to hunger.…”
Section: Evaluation Instrumentmentioning
confidence: 99%
“…The self-report Three-Factor Eating Questionnaire (TFEQ) was already applied to assess the impact of LAGB, VBG and RYGBP [11][12][13][14][15][16] on three dimensions of eating behavior: cognitive restraint of eating, disinhibition of eating and susceptibility of hunger. In laparoscopic sleeve gastrectomy (LSG), another restrictive bariatric procedure [17][18][19][20][21][22][23][24], the TFEQ as a validated and reliable instrument has not been used for the evaluation of the impact on eating behavior so far.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, obesity may have an impact on key aspects of health-related quality of life (HRQOL), with research showing that obese patients seeking bariatric surgery are more likely to be impaired in terms of HRQOL than are nontreatment-seeking obese patients [2][3][4][5][6][7]. In this context, the advent of anti-obesity medications and surgical treatments [8,9] has shown that weight reduction is associated with an improvement in HRQOL [10,11], and therefore, its assessment has become important. Although generic HRQOL assessment instruments are available, the use of obesity-specific assessment tools is recommended, since they are capable of assessing particular aspects of quality of life [12].…”
Section: Introductionmentioning
confidence: 99%